Missa da Luz uma experiência de na Paraíba de acordo com a teoria geral do imaginário: um estudo etnográfico - Abrantes, Andréa Maranhão de Oliveira Dantas (2019)
The purpose of this dissertation, the Mass of Light: An example of faith in northeastern Brazil, aims to analyze the religious phenomenon present in this celebration, which attracts every thursday thousands of people from various communities belonging to the Archdiocese of Paraiba and neighboring dioceses, being considered the largest Catholic celebration permanently, existing. To achieve our goals, we seek the method through Imaginary Theory as a way to better develop our research, starting to observe the celebration, through anthropology, sociology, seeking to understand the symbols that are present in the Queen Mother Shrine, expressed by the celebration every week, where they go to live and celebrate their faith, seeking to contribute to the understanding of the existing semantic basins that only with the collaboration of Imaginary Theory was possible allowing us an approach where reason and faith analyzed and their impact on the lives of the faithful.